Dampak pembelajaran daring di masa pandemi terhadap pemahaman materi mahasiswa FKIP UNTIRTA - Pambudi, Gigih Adhi; Subhan Widiansyah (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Online learning is an alternative that can overcome the problem of disrupting the conventional learning process during the Covid-19 pandemic. In online learning, there are many obstacles faced by students or lecturers. The problem that students often face is network problems. A bad network connection will affect the message or explanation of the material delivered by the lecturer. With network disruption, students often have difficulty understanding the explanations given by lecturers, because the voices they hear tend to be less clear. Therefore, this research aims to explain in detail the impact of online learning on the understanding of FKIP Untirta students during the Covid-19 pandemic. Using a descriptive qualitative approach in the form of observations. With the subject of observation by FKIP Untirta students. The discussion focuses on the impact that online learning has on students' understanding of the material. The results of this research show the influence of online learning on students' understanding of material, the problems students face and the obstacles in carrying out online learning. It can be concluded that online learning greatly influences FKIP Untirta students' understanding of the material.